PROGRAM SIRKUMSISI DI PONDOK IMAM SYAFI’I DESA TAPAN KECAMATAN KEDUNGWARU KABUPATEN TULUNGAGUNG DALAM UPAYA MENINGKATKAN KESEHATAN ORGAN REPRODUKSI - Angga Miftakhul Nizar; Farida Farida; Yitno Yitno (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2022)
Circumcision is a medical procedure performed on boys to improve their reproductive health. Circumcision requires financial and emotional preparation for children, so the implementation of this community service activity aims to provide quality free circumcision facilities for children in Tapan Village, Kedungwaru District, Tulungagung Regency, which was attended by 42 children with education spread from preschool to high school, with ages the lowest was 4 years and the highest age was 17 years, and most of the children participated in this activity on their own volition. Circumcision activities went smoothly and there were no abnormalities in the penis in the form of phimosis, necrosis, massive bleeding, and the like.